2020
DOI: 10.1159/000511251
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Esophageal Squamous Papillomatosis: A Rare Disease Associated with Acanthosis Nigricans and Tripe Palms

Abstract: Acanthosis nigricans with tripe palms is one of the skin manifestations of systemic conditions, as well as internal malignancy. There have been reports of this paraneoplastic condition’s association with orocutaneous papillomatosis, but investigations into its relationship with diffuse esophageal papillomatosis are scarce. We report a case of acanthosis nigricans with tripe palms that was associated with diffuse esophageal squamous papillomatosis. A 40-year-old Thai woman with underlying systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Most reported patients are asymptomatic. With the rarity of diffuse papillomatosis in literature, the standard surveillance or treatment strategies have not been established (1). Cutaneous papillomas can be found in 70% of patients with CS (2).…”
mentioning
confidence: 99%
“…Most reported patients are asymptomatic. With the rarity of diffuse papillomatosis in literature, the standard surveillance or treatment strategies have not been established (1). Cutaneous papillomas can be found in 70% of patients with CS (2).…”
mentioning
confidence: 99%
“…When tripe palms are present with malignant acanthosis nigricans, they reflect up to a one-third incidence of gastrointestinal malignancy. 12,13 Despite the individual presentation of these paraneoplastic signs in a variety of malignancies, synchronous presentation is rare. A brief literature review only identified 6 cases of concurrent acanthosis nigricans, tripe palms, and progressive mucocutaneous papillomatosis with an underlying gastrointestinal malignancy.…”
mentioning
confidence: 99%